2020
DOI: 10.3332/ecancer.2020.1046
|View full text |Cite
|
Sign up to set email alerts
|

Reactions and countermeasures of medical oncologists towards the incoming COVID-19 pandemic: a WhatsApp messenger-based report from the Italian College of Chief Medical Oncologists

Abstract: Background: This descriptive, unplanned investigation has been undertaken to report reactions, attitudes and countermeasures which have been put in place and implemented by medical oncology units facing the COVID-19 outbreak in Southern Italy.Materials and methods: Data have been retrospectively obtained from the time-related analysis of conversations via a WhatsApp messenger-based group chat between the medical directors belonging to the Italian College of Medical Oncology Directors. Overall number, intensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…However, positive emotions, such as trust, also increased with time. 20 In our group, female, younger physicians with less experience duration were more likely to worry about the disease and report a negative impact of the pandemic on their well-being. The concerns about healthcare providers’ emotional well-being were raised by many authors highlighting the need for a systemic approach to prevent and recognize problems early and intervene appropriately.…”
Section: Discussionmentioning
confidence: 65%
“…However, positive emotions, such as trust, also increased with time. 20 In our group, female, younger physicians with less experience duration were more likely to worry about the disease and report a negative impact of the pandemic on their well-being. The concerns about healthcare providers’ emotional well-being were raised by many authors highlighting the need for a systemic approach to prevent and recognize problems early and intervene appropriately.…”
Section: Discussionmentioning
confidence: 65%
“…They also described the modality to manage surgical interventions and radiation therapy and to conduct clinical trials. A single investigation reported the reactions, attitudes, and countermeasures undertaken by medical oncology units facing the COVID-19 outbreak in southern Italy [ 20 ]. This study retrospectively obtained data from the time-related analysis of conversations via a phone messenger-based group chat between oncologists and patients, and concluded that the use of an instant-messaging system seemed to be a useful tool to share news and reactions between medical oncologists to rapidly implement necessary health measures and provide answers to most cancer patients’ needs.…”
Section: Discussionmentioning
confidence: 99%
“…These unique set of challenges lead to the formal implementation of readily accessible technologies, such as video conference software and IMAs (Inc. WhatsApp), in delivering the core medical curricula by many institutions. A recent review evaluating the effectiveness of this emerging educational paradigm in an uncertain COVID-19 era, concluded that "virtual tools can be used by both learners and educators to achieve a shared goal of providing effective and efficient medical education", but also adds that they are not without their inherent limitations [5]. Consequently, further research is needed to determine whether IMAs and other virtual platforms are an effective long-term substitute for in-person learning or if they should simply remain an adjunct to the traditional educational paradigm.…”
Section: Clinical Attachmentsmentioning
confidence: 99%